2019
DOI: 10.1002/jsfa.10052
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae Schizochytrium limacinum as an alternative to fish oil in enriching table eggs with n‐3 polyunsaturated fatty acids

Abstract: BACKGROUND The research deals with the addition of microalgae Schizochytrium limacinum as an alternative to fish oil in a feed‐mixture for laying‐hens and its effect on the deposition of n‐3 polyunsaturated fatty acids (n‐3‐PUFAs) [α‐linoleic acid (ALA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)] in the lipids of egg yolks. In the study, 240 Tetra SL laying hens housed in enriched cages were used, divided into six groups, each in five repetitions. Groups E1, E3 and E5 were given 0.5%, 1.0% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Meanwhile, our study has demonstrated that Schizochytrium sp. residue, a byproduct in commercial DHA algal oil production, was an economical and promising source to enrich eggs with n-3 PUFA-lipids, especially the DHA-lipid without any compromise in their enrichment efficiencies compared to relatively expensive whole microalgae cells. , It could achieve the comparative level of total n-3 PUFA-lipid in egg yolk as dietary flaxseed, but the contents of longer-chain PUFA-lipids, which are more beneficial than ALA, were remarkably higher (79 vs 28% of the total PUFA-lipid) (Figure A). Among these n-3 PUFA-lipids, DHA-GPs have received increasing attention from nutritionists and pathologists due to their superior bioactivity and bioavailability when compared to DHA-GLs and DHA-ethyl ester. , They exhibit the dual effects of DHA and GPs and have been reported to play vital roles in brain and retina development and treatment of multiple diseases. The n-3 PUFA-enriched eggs obtained from hens fed with the Schizochytrium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, our study has demonstrated that Schizochytrium sp. residue, a byproduct in commercial DHA algal oil production, was an economical and promising source to enrich eggs with n-3 PUFA-lipids, especially the DHA-lipid without any compromise in their enrichment efficiencies compared to relatively expensive whole microalgae cells. , It could achieve the comparative level of total n-3 PUFA-lipid in egg yolk as dietary flaxseed, but the contents of longer-chain PUFA-lipids, which are more beneficial than ALA, were remarkably higher (79 vs 28% of the total PUFA-lipid) (Figure A). Among these n-3 PUFA-lipids, DHA-GPs have received increasing attention from nutritionists and pathologists due to their superior bioactivity and bioavailability when compared to DHA-GLs and DHA-ethyl ester. , They exhibit the dual effects of DHA and GPs and have been reported to play vital roles in brain and retina development and treatment of multiple diseases. The n-3 PUFA-enriched eggs obtained from hens fed with the Schizochytrium sp.…”
Section: Discussionmentioning
confidence: 99%
“…A combined effect of the probiotic Lactococcus lactis and the prebiotic A. limacinum biomass, fed to fish, induced positive effects on their growth and immunity (Sun et al, 2019). A. limacinum biomass is commercialised and was successfully used as alternative for fish oil in feeding laying hens for the enrichment of table eggs with n-3 fatty acids (Kralik et al, 2019).…”
Section: Zygosaccharomyces Rouxiimentioning
confidence: 99%
“…Studies involving the incorporation of microalgae in diets supplied to laying hens have also shown promising results, mainly in egg quality. The fatty acid profile of both yolk and egg white showed improvements without harming animals and even improving zootechnical indexes (Manor et al, 2019;Ao et al, 2015;Kralik et al, 2020;Ginzberg et al, 2000). There was a decrease in the yolk cholesterol contents (Park et al, 2015) and an intensification of its colour (Anderson et al, 1991).…”
Section: Ducksmentioning
confidence: 99%